Effect of pulsed ultrasound on osteoreparation progress in the area of implantation of titanium samples (experimental study) - Malyshkina, Svitlana; Makolinets, Vasyl; Nikolchenko, Olga; Vishnyakova, Iryna; Grashchenkova, Tamara (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Purpose: to study osteoreparative process in experiment on rats in region of implantation of titanium samples after exposure of pulsed ultrasound with oscillations’ intensity of 0.4 and 0.7 W/cm2 applied since the third day after surgery. Materials: fragments of femurs with titanium (BT-16) implants of 57 six-month rat became as a material of study. We used morphological and morphometric methods of investigation. We determined area of the newly formed tissue (granulation, fibroreticular and bone) around the implants, active osteoblastic surface (length of bone trabeculae occupied by active osteoblasts), the index of osseointegration (the length of contact surface of the implant with the bone tissue), the thickness of the connective tissue capsule around the perimeter of implant removed. Results: it was found that the pulsed ultrasound accelerates restructuration of granulation tissue to fibroreticular one with its differentiation in osteogenic direction. Presence of significant osteoblasticdifferon cell density in this tissue also indicates to this fact. Ultrasound with oscillations’ intensity of 0.4 and 0.7 W/cm2 stimulates bone formation in area of implantation which confirmed by data of active osteoblastic surface, area of newly formed bone tissue, and index of osteointegration which were larger in animals of the experimental groups than in control ones in all terms of the research. Conclusions: more pronounced positive effect of ultrasound on osteoreparation was in the case of the oscillations’ intensity of 0.4 W/cm2 which is confirmed by data of area of newly formed bone and osseointegration index obtained at 14, 30 and 45 day of study, and which is veraciously higher than in the case of using of ultrasound intensity of 0.7 W/cm2. Results of the study will be used for substantiation of the development of indications and methods of application of ultrasound in patients after reconstructive surgery with using of fixing devices.